Evaluation of selected academic libraries in Manila - Reyes, Julius Romil O.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2010)
Evaluation is the key for library administration to see the library's improvements and inefficiencies. As evaluation is proven to be important, this research aims to determine the current state of academic libraries in Manila using holistic evaluation based on the 2000 Library Standards set by the Philippine Association of Academic and Research Librarians (PAARL). Holistic evaluation assesses two perspectives in a library; internal perspective (based on the procedures and standards imposed in libraries, recorded interactions, etc.) and external perspective (users' evaluation of library system and use of library). Internally, the research evaluated the academic libraries' collection, personnel, budget, physical space and facilities, and services. Externally, users evaluated their perspective libraries in terms of collection, personnel, service, and physical space and facilities. Eight academic libraries participated in the research: Centro Escolar University (CEU), Colegio de San Juan de Letran (CSJK), De La Salle University (DLSU), La Consolacion College (LCC), Lyceum of the Philippines University (LPU), Mapua Institute of Technology (MIT), Philippine Normal University (PNU), and St. Scholastica's College (SSC). Recommendations were given to improve the 2000 PAARL Library Standards and the academic libraries.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Academic libraries -- Philippines -- Manila -- Evaluation